Metode Penetapan Hukum Dalam Berfatwa - Ahmad Mukhlishin; Aan Suhendri; Muhammad Dimyati (Al-Istinbath: Jurnal Hukum Islam, 2018)
Fatwa is the answer to the problem that arises, usually respond to contemporary things. This can be seen from a series of fatwa issued by the MUI. from the problem golput, cigarettes, pre-wedding photos, motorcycle taxi women and many other things. Fatwa is a very urgent case for humans because not everyone is able to explore the laws of the Shari'a. Or it can be concluded that the fatwa is an explanation of Sharia law on various issues that occur in the midst of society. Therefore, given the importance of the position of the fatwa, it should be done that the people do not ignore the fatwas issued by the Fatwa scholars born because of the consideration of the benefit of the ummah or mashalihul ummah, and in this paper will be discussed about the methods of law enforcement in berfatwa. One of the conditions for determining fatwas is that they must fulfill the methodology (manhaj) in teaching, because it establishes fatwas without regard to manhaj including those which are prohibited by religion. Establish a fatwa based solely on the necessity (li al-hajah), or because of the benefit (li al-mashlahah), or because the essence of religious teachings (li maqashid as-syari'ah), with no adhering to nushus syar'iyah, including the excessive group (ifrathi). Within the scope of the fatwa there are some important things that must be noticed by a mufti (giver of fatwas) and a mustafti (the person who asks fatwas) so that the resulting fatwa can be useful in solving a problematika. For the sake of perfection a fatwa of mustafti must use some method which must be consumed in solving problem which in ijtihadi at that time, like method bayani, ta'lili and termi.